IMPLEMENTASI SMARTKEY PADA SEPEDA MOTOR MENGGUNAKAN E-KTP - Supendi, Yiyi (Universitas Multi Data Palembang, 2022)
There are so many motorbikes in this era with varying prices that almost everyone has a motorbike, and motorbike theft crimes often occur everywhere, because of this there should be a security device on the motorbike lock by making a smartkey device on the motorbike. using E-KTP as the key. The system is designed using an Arduino Atmega168p and an RFID Reader as a tool to command the relay to connect electricity. The control system can turn electricity on/off just with an E-KTP, making it easier for adult motorbike owners and to stay away from children who are not yet old enough to use a motorbike. Keywords: RFID, e-KTP, Arduino Nano, Arduino IDE, Relay, Jumper Cable, Buzzer.